The effect of a web-based lifestyle intervention on nutritional status and physical activity on prevention of COVID-19: a randomized controlled trial in women's empowerment - Pourfarzi, Farhad; Kamran, Aziz; Zare, Maryam; Mohammadshahi, Jafar (Frontiers in Nutrition, 2024)
Abstract Background: Healthy dietary intake and physical activity affect the immune systems. The present study aimed to investigate the effects of a web-based lifestyle intervention on nutritional status, physical activity, and prevention of COVID-19. Methods: Three hundred- three women 30 to 60 years who did not have COVID-19 in the City of Ardabil participated in this study. Participants were randomized into an intervention (n=152) or control group (n=151). The intervention group received eight online educational sessions focusing on a healthy diet and physical activity via the website. The control group received the usual instructions. Outcomes were nutritional status, physical activity, Immunoglobulin G (IgG) and Immunoglobulin M (Ig M) antibodies titers against the virus. They were evaluated at the baseline, after 4 and 12 weeks. Results: Significant improvements in weight (P<.001), BMI (P<.001), carbohydrate (P=.016, P=.010), and fat intake (P=.007, P=.002) was found for the intervention group compared to control group during study. There was a significant time x group interaction in 4 weeks in energy intake (Beta=-206.5, 95% CI -377 to -35.9, P=.018). Total physical activity was increased during the study (P<0.001) for both groups. In terms of IgG, 4.8 % of the intervention (P=.002) and 8.7 % of the control groups (P<.001) were positive in 12 weeks. In the follow-up, 5.6% of the intervention group and 7.1% of the control group were positive in IgM. Conclusion: The web-based lifestyle intervention may improve nutritional status and physical activity; and have the potential to reduce the risk of contracting a COVID-19 infection.